THE USE OF 3D VISUALISATION FOR URBAN DEVELOPMENT, REGENERATION AND SMART CITY DEMONSTRATION PROJECTS: BATH, BUCKINGHAMSHIRE, AND MILTON KEYNES - Bailey, Stewart; Deshpande, Advait; Miller, Alby (BDC. Bollettino Del Centro Calza Bini, 2014)
The aim of this paper is to discuss three different case studies related to the use of 3D visualisation for projects focussing on urban development, regeneration, and Smart City demonstrations. With each of the case studies, the problem statement, the approach adopted for 3D visualisation, and the outcome is covered. The paper concludes by discussing what 3D visualisation offered to each project. The paper discusses how in order to effectively use 3D visualisation the approach needs to be adapted according to the problem statement. Depending on the project requirement, 3D visualisation is likely to serve multiple purposes in urban development, regeneration, and Smart City demonstration projects. The paper suggests that the use of 3D visualisation adds an extra dimension to presenting data and also provides an effective tool for analysing the data. Keywords: 3D visualisation, urban development and regeneration, Smart City